Seven skills of media literacy - Potter, W. James (Los Angeles, CA : SAGE Publications, Inc., 2019)
KEY FEATURES: The only book that provides a thorough description of the essential skills of media literacy. Each skills chapter provides a set of step-by-step exercises to help readers practice their skills in a variety of situations. A distinctive audience-centered approach- as opposed to the traditional media industry approach- keeps the book focused on the everyday experiences of students.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Media literacy